Konsep Tazkiyatun Al-Nafs Dan Implikasinya Terhadap Pendidikan Islam (Studi Literatur Terhadap Kitab Terjemah Al-Mustakhlah Fii Tazkiyatil Anfus Imam Al-Ghazali) - Sri Rezeki Islami, Muhammad Saleh, Zaifatur Ridha (Khazanah : Journal of Islamic Studies, 2023)
The background of this research was that one of the Islamic education figures who made a major contribution to education was Al-Ghazali. The educational thought put forward by Al-Ghazali has a religious-ethical pattern. This pattern is influenced by his mastery in the field of Sufism and his thinking which places more emphasis on ethical and spiritual aspects. The purpose of education is to get closer to Allah and get happiness in this world and the hereafter. Al-Ghazali's thoughts in the field of education give their own style in Islamic education. Al-Ghazali's thoughts on Tazkiyatil Anfus are a treasure of Islamic scholarship that should be inherited and studied by the younger generation of Muslims, especially among Muslim students. The objectives of this research are: To find out the Implications of the Tazkiyatun Al-Nafs Concept for Islamic Education. This study uses document library research design for data collection using documentation with work studies. The result of this research is that education according to Al-Ghazali is part of tazkiyatun nafs, and knowledge is seen as a tool to illuminate the heart and guide the mind to glory. According to Al-Ghazali, the morals of students can basically be trained, directed, changed, and formed through education. Al-Ghazali put forward ten concepts of tazkiyatun nafs in the context of education education, namely: prioritizing the purity of the soul over despicable morals from disgraceful traits, reducing contact with the busy world, willing to stay away from family and homeland to study knowledge, not arrogant because of knowledge and not opposing the teacher, keeping oneself from listening to different human opinions, not abandoning commendable sciences, acquiring knowledge gradually, knowing the reasons that can lead to knowing the glory of knowledge, and knowing the relationship of science to its goals.